Multiresistant zoonotic pathogens isolated from goat milk in Northeastern Brazil. (December 2021) - Aragão, Breno Bezerra; Trajano, Sabrina Cândido; de Oliveira, Raylson Pereira; Sobral da Silva, Débora Mirelly; de Carvalho, Rafaella Grenfell; Juliano, Maria Aparecida; Pinheiro Junior, José Wilton; Mota, Rinaldo Aparecido
Highlights: Goat infectious mastitis, a danger to human and animal health. Occurrence of zoonotic pathogens emerging multi resistant carried by goat milk. Comprehensive study on Staphylococcus spp. isolated from milk goat in Brazil. Detection of Staphylococcus spp. resistant to methicillin and vancomycin. Abstract: Dairy goats play a significant role in socio-economic, cultural, and nutritional development in many countries. This study aimed to identify multiresistant zoonotic pathogens causing mastitis in goats, in addition to characterizing them for the presence of resistance genes and phenotypic resistance. A total of 714 milk samples from 357 lactating goats in 12 farms in the Northeast region of Brazil were analyzed. The isolates were submitted to Matrix Associated Laser Desorption-Ionization - Time of Flight to identify bacterial species, Polymerase Chain Reaction (PCR) to search for resistance genes, and an antibiogram to evaluate the phenotypic profile of antimicrobial resistance. A total of 214 pathogens were identified and bacterial prevalence was 83.29 % (178/214) Staphylococcus spp.; 6.50 % (14/214) Micrococcus luteus ; 3.73 % (8/214) Corynebacterium spp.; 2.80 % (6/214) Bacillus spp.; 1.38 % (3/214) Escherichia coli ; 0.92 % (2/214) Enterobacter cloacae ; 0.46 % (1/214) Aerococcus viridans ; 0.46 % (1/214) Morganella morganii; and 0.46 % (1/214) Turicella otitidis . As for gene frequency, 64.60 % (115/178) of the isolates carried the blaZ gene; 37.07 % (66/178) norA ; 22.47 % (40/178) tet (L); 16.85 % (30/178) tet (M); 14.04 % (25/178) norB ; 8.42 % (15/178) vanA ; 7.30 % (13/178) msrA ; 6.41 % (5/178) tet -38; 4.49 % (8/178) norC ; 2.25 % (4/178) mecA; and 0.56 % (1/178) vanB . Emerging multiresistant zoonotic pathogens are present in the goat milk production chain, especially the coagulase-negative Staphylococcus species that pose a risk to human and animal health.